10-річні результати хірургічного лікування хвороби двостулкового аортального клапану (2003–2012 рр.) - Кравченко, І.М.; Ситар, Л.Л.; Кравченко, В.І.; Дикуха, С.О.; Третяк, О.А.; Захарова, В.П.; Пантась, О.В.; Дуплякіна, В.Е.; Ларіонова, О.Б.; Чумак, О.С.; Книшов, Г.В. (Таврический медико-биологический вестник, 2013)
На основании собственного опыта отработана тактика лечения разнообразных вариантов течения
болезни двустворчатого аортального клапана. Выполнен анализ результатов хирургического лечения
каждого из вариантов течения болезни. Congenital bicuspid aortic valve (BAV) – the most frequent lesion of cardiovascular system, its prevalence in
the general population constitutes from 0,9 to 2,0%. Ascending aorta aneurysm forming were observed in 33,5%
patients with BAV, among them in 10,0% with dissection. Operative treatment of patients with BAV permitted
to obtain good remote results in 85,4% patients.